2017
DOI: 10.26891/jik.v4i2.2010.79-88
|View full text |Cite
|
Sign up to set email alerts
|

The Link Of Epstein Barr Virus Infection And Rheumatoid Arthritis Immunopathogenesis

Abstract: The cause of Rheumatoid Arthritis (RA) remains unknown. Environmental factors as well as genetic factors have been linked to pathogenesis of RA, in particular Epstein Barr Virus (EBV) infection. Since clinical onset of RA is long time after primary viral exposure, it is still difficult to demonstrate the direct link of EBV infection with RA pathogenesis. However, the high levels of antibodies against several EBV proteins detected in RA patient sera, the molecular mimicry of EBV proteins with RA susceptible all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…This result is similar to other studies that demonstrated a link between EBV infection and RA pathogenesis. [16][17][18][19] One of the chronic autoantibody responses related to the development of RA is the anti-EBV antibody response. 20 Other studies have provided evidence about the association of EBV with RA, and have shown EBV to be the cause of RA.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to other studies that demonstrated a link between EBV infection and RA pathogenesis. [16][17][18][19] One of the chronic autoantibody responses related to the development of RA is the anti-EBV antibody response. 20 Other studies have provided evidence about the association of EBV with RA, and have shown EBV to be the cause of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies speculated that EBV infection is strongly associated with RA from different parts of the world [ 7 , 10 , 11 ]. In Pakistan, EBV has been detected in various lymphoma patients from different areas [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%